STIMULASI AUDITORI PADA PASIEN CEDERA KEPALA DENGAN PENURUNAN KESADARAN - Septiany, Maulidya; Kosasih, Cecp E.; Rahayu, Urip (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2019)
Traumatic brain injury (TBI) is a disease that is able to change a person’s level of consciousness and causedeath with a case fatality rate (CFR) of 4.37%. In addition, the impact of these injuries can also causecognitive damage and physical function. Giving sensory stimulation in the form of auditory stimulation asearly as possible is very important for survival, quality of life and long-term prognosis in head injurypatients because hearing is the last sensory function to function in decreased consciousness. The aim of thisstudy was to determine the effect of auditory stimulation on head injury patients with decreasedconsciousness. This study is a literature review. The databases used are ProQuest, CINAHL, PsycINFO,Google Scholar, PubMed, EBSCO and ScienceDirect with the keywords used are Traumatic Brain Injury,Auditory Stimulation, Comatose Patient, Level of Consciousness. The inclusion criteria were articlespublished in 2008-2018, Randomized Clinical Trial (RCT) studies, the study sample was head injurypatients with reduced awareness, the intervention provided was in the form of auditory stimulation andarticles written in English. The results of this literature study obtained 6 research articles that were inaccordance with the objectives and review criteria. The results of the study concluded that auditorystimulation in head injury patients had a significant effect on increasing consciousness status. Therefore,auditory stimulation can be recommended as an additional non-pharmacological therapy for head injurypatients who experience decreased consciousness.